Hygroscopic additive-modified magnesium sulfate thermochemical material construction and heat transfer numerical simulation for low temperature energy storage. Issue 14 (21st March 2022) - Li, Shi-Jie; Yang, Xiang-Yu; Deng, Li-Sheng; Fu, Yong-Chun; Pang, Ming-Jun; Dong, Ti; Yu, Yi-Song; Su, Ling-Na; Jiang, Shang
Abstract : Construction of a high performance hydrophilic magnesium sulfate composite thermal energy storage material and numerical simulation of its heat transfer behavior. Abstract : In this research, the core objective is to explore the effect of super-absorbent polymer material (poly(sodium acrylate)) on the heat storage performance of magnesium sulfate and to investigate the heat transfer behavior of 13X-zeolite, nano-aluminum oxide (nano-Al2 O3 ) and poly(sodium acrylate) modified magnesium sulfate in a reactor. Finally it provides support for future material and reactor design. All characterizations and performance tests were done in the laboratory and a numerical simulation method was used to investigate the heat transfer behavior of the reactor. Through hydrothermal treatment, bulk MgSO4 ·6H2 O was changed into nanoparticles (200–500 nm) when composited with poly(sodium acrylate), 13X-zeolite and nano-Al2 O3 . Among these materials, MgSO4 ·6H2 O shows the highest activation energy (36.8 kJ mol −1 ) and the lowest energy density (325 kJ kg −1 ). The activation energy and heat storage energy density of nano-Al2 O3 modified composite material MA-1 are 28.5 kJ mol −1 and 1305 kJ kg −1, respectively. Poly(sodium acrylate) modified composite material, MPSA-3, shows good heat storage energy density (1100 kJ kg −1 ) and the lowest activation energy (22.3 kJ mol −1 ) due its high water-absorbing rate and dispersing effect. 13X-zeolite modified composite material MZ-2 shows lower activation energy (32.4 kJ mol −1 ) and the highest heat storage density (1411 kJ kg −1 ), which is 4.3 times higher than that of pure magnesium sulfate hexahydrate. According to the heat transfer numerical simulation, hygroscopic additives could prominently change the temperature distribution in the reactor and efficiently release heat to the thermal load side. The experimental and numerical simulation temperatures are similar. This indicates that the result of the numerical simulation is very close to the actual heat transfer behavior. This reactor could output heat at around 50 °C and absorb heat in the range of 100–200 °C. All these results further prove the strategy that thermochemical nanomaterial synthesis technology combined with material-reactor heat transfer numerical simulation is feasible for future material and reactor design.